Sanções políticas tributárias: análise dos embaraços à atividade econômica empresarial e do dever de indenizar do Estado - Toledo, Ana Flávia Christofoletti de (2018)
The present dissertation discusses the political penalties in tax matters that embarrass the business economic activity, which causes the liability of the State to indemnify. Beginning with the three constitutional principles established by the articles 5th, 37 and 150, this paper seeks to align the limits of the State in its regular exercise of the right to tax. It shall be analyzed subsequently the concept of political penalty and its differences with tax penalty, scenarios in which are admitted its applicability in the analyses of the Federal Supreme Court, illustrating how this topic is up to date and sheltered by the Judiciary. Based on this, the present work restricts its coverage to focus on the protest of Active Debt Certificate (Law No. 9.492/1997), enrollment in the Registry of Outstanding Credits of Federal Agencies and Entities (Law No. 10.522/2002), issuance of Negative Certificate of Debts (articles 205 and 206 CTN) and notation of pre execution (Law No. 13.606/2018), which are political penalties that disturbs the business economic activity due to the difficulty they may cause in the cash flow of an entity, to the point of unfeasible its continuity. As a consequence of it, and once the State is using its police authority in excess and is abusing of its rights, it’s necessary the accountability of the State from a civil perspective. Although, after the analyses of court decisions, this dissertation will exam how the indemnity duty of the state, as a result of the political penalty, is not frequently required by the tax payers and poorly exploited by the Judiciary